Working well : women's experience of managing psychological wellbeing as sex workers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Aotearoa/New Zealand - Marie, Janet (Massey University, 2009)
Despite evidence to the contrary, policy makers, some researchers and many who provide health and social services to sex workers continue to reflect and reinforce the notion that sex workers are dysfunctional and constitute a threat to public health. This thesis presents the results of a study which explicitly examined how indoor sex workers look after their psychological wellbeing. Twelve participants (who had worked as sex workers for at least 3 years) took part in semi-structured interviews and discussed how they looked after themselves both at work and in their wider social context. Interviews were transcribed and analysed using interpretative phenomenological analysis. Two main themes emerged from the data. The first, “doing sex work”, relates to workplace practices. The second theme, “being a sex worker”, relates to how the women understand their experience of being a sex worker in their social context and how they care for themselves in this arena; also apparent in this theme are aspects related to entry and exit of the industry. All participants took part in the study to increase understanding of and social justice for sex workers. Most of the participants see sex work as having a positive contribution to their personal growth. The findings show that participants are resilient and employ self-care practices that are commonly used by many in occupations that deal with people or who are stigmatised in some way. Major conclusions drawn from the study are that working in a supportive environment, prior understandings of sex work, personal traits and reasons for entering the sex industry are closely related to positive psychological wellbeing.
Keywords: Sex industry; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380105 Social and community psychology